New ligands of the cellular retinoic acid-binding protein 2 (CRABP2) suggest a role for this protein in chromatin remodeling - Rossetto, Daniella de Barros [UNESP] (2014)
Retinoic acid (RA) regulates the transcription of a series of genes involved in cell proliferation, differentiation and apoptosis by binding to the RA Receptor (RAR) and Retinoid X Receptor (RXR) heterodimers. The cellular retinoic acid-binding protein 2 (CRABP2) is involved in the transport of RA from the cytosol to specific RA receptors in the nucleus, acting as a coactivator of nuclear retinoid receptors. In order to have a better understanding of the role of CRABP2 in RA signaling, we used the yeast two-hybrid system as a tool for the identification of physical protein-protein interactions. Twenty-three putative CRABP2-interacting proteins were identified by screening in the presence of RA, five of which are related to transcription regulation or, more specifically, to the process of chromatin remodeling: t-complex 1 (TCP1); H3 histone, family 3A (H3F3A); H3 histone, family 3B (H3F3B); β-tubulin (TUBB) and SR-related CTD-associated factor 1 (SCAF1). These results suggest a more direct role for CRABP2 in chromatin remodeling and may be a starting point for the elucidation of the fine-tuning control of transcription by RA receptors.